2012
DOI: 10.1111/j.1365-2613.2012.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial lymphocytes, goblet cells and VIP‐IR submucosal neurons of jejunum rats infected with Toxoplasma gondii

Abstract: Summary Toxoplasma gondii (T. gondii) crosses the intestinal barrier in oral infections and can lead to changes in different cell types, including the neurons located there. In the gastrointestinal system, the autonomous nervous system component that regulate blood flow and mucous secretion is the submucosal plexus. The aim of this study was to examine the effects of T. gondii infection on intraepithelial lymphocytes (IELs), goblet cells and submucosal neurons that are immunoreactive to vasoactive intestinal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 63 publications
(68 reference statements)
1
20
0
1
Order By: Relevance
“…Our previous studies have shown that the infection can cause changes in enteric neurons and in intestinal wall (da Silva Pde et al, 2010;Hermes-Uliana et al, 2011;Odorizzi et al, 2010;Sant'Ana et al, 2012;Shiraishi et al, 2009;Sugauara et al, 2008Sugauara et al, , 2009). These changes depend on the parasitic stage ingested, the duration of the infection, the host species and the part of the gastrointestinal tract evaluated.…”
Section: Introductionmentioning
confidence: 93%
“…Our previous studies have shown that the infection can cause changes in enteric neurons and in intestinal wall (da Silva Pde et al, 2010;Hermes-Uliana et al, 2011;Odorizzi et al, 2010;Sant'Ana et al, 2012;Shiraishi et al, 2009;Sugauara et al, 2008Sugauara et al, , 2009). These changes depend on the parasitic stage ingested, the duration of the infection, the host species and the part of the gastrointestinal tract evaluated.…”
Section: Introductionmentioning
confidence: 93%
“…Our research group has sought to understand this relationship for more than a decade. We have shown that the infection can compromise the intestinal structure and innervation, even in immunocompetent individuals with no classic clinical signs of toxoplasmosis . We observed local inflammation that was possibly induced by the presence of the parasite in the organ, reflected by the presence of tissue cysts and parasitic DNA .…”
Section: Introductionmentioning
confidence: 75%
“…In rats, after oral infection with T. gondii oocysts, Sant'Ana et al [507] found a marked reduction in the number of goblet cells producing neutral mucins (PAS+) and sulphomucins (AB pH 1.0) as compared with control animals, and these changes reflected production of a more fluid mucous (Table 34). The number of vasoactive intestinal peptide (VIP-IR) submucosal neurons as well as the area of the VIP-IR neuronal cell bodies also decreased significantly compared with control rats (667 ± 6.98 vs. 856 ± 14.89 per 1.74 mm 2 of the jejunum, p<0.05, and 317.29 ± 9.28 vs. 404.24 ± 11.10 µm 2 , p<0.05, respectively).…”
Section: T Gondii Infectionmentioning
confidence: 99%
“…The number of vasoactive intestinal peptide (VIP-IR) submucosal neurons as well as the area of the VIP-IR neuronal cell bodies also decreased significantly compared with control rats (667 ± 6.98 vs. 856 ± 14.89 per 1.74 mm 2 of the jejunum, p<0.05, and 317.29 ± 9.28 vs. 404.24 ± 11.10 µm 2 , p<0.05, respectively). All these abnormalities indicated that oral T. gondii infection caused alterations in the chemical composition of the intestinal mucous and reduction in the number of submucosal neurons associated with atrophy of the remaining neurons in this cell subpopulation [507]. In this context, it is suggested that the morphological changes reported in duodenal atresia (a well known neonatal intestinal disease), such as the neuronal cells decreased in number and size, the circular musculature moderately-to-severely hypertrophic, and the interstitial cells of Cajal decreased even around the myenteric plexus [508], were due to chronic latent T. gondii infection.…”
Section: T Gondii Infectionmentioning
confidence: 99%